"A World Complete Without Me": Writing Cinema in Paul Auster's The Book of Illusions. Issue 4 (8th August 2019) - Zhang, Meiping
ABSTRACT: Paul Auster's creative practice involves a tendency to transcend the boundaries between different mediums, as exemplified by his cinematographic fiction. Although relevant research has started to gain traction in recent years, there are still few in-depth analyses of the medium of film, its implication in the verbal medium, and its connection with the themes explored in an individual novel of Auster's. Drawing on Stanley Cavell's film philosophy, the present essay attempts to explicate the meaning and function of writing cinema in The Book of Illusions . Starting with several fundamental issues concerning viewing and writing—including the philosophical basis on which cinematic experience and its expression can possibly be construed—this essay delves further into their connections with one of the ethical questions presented in the novel: how can and should one relate to another's life and work? From the viewpoint of Cavellian film philosophy, the question may be phrased this way: how can and should I, a viewer, respond to "a world complete without me"?